Giant Wilms tumor in a child: Safe radical nephrectomy - Moaied A. Hassan (Elsevier, 2020)
Wilms tumor is the second most common intraabdominal malignancy, and the most common malignant renal tumor in the pediatric age group, accounting for more than 95% of all renal tumors in children. In the last few decades, a significant improvement has been reported in the prognosis of patients with Wilms tumors due to adopting a multidisciplinary treatment approach consisting of surgery, chemotherapy and radiotherapy based on results of sequential trials. Regardless the kind of protocol followed to treat children with Wilms tumor, surgery remains an essential and fundamental step in the overall management. Well performed surgeries following rules of safe tumor excision, evaluation of disease extension and lymph nodes sampling will determine the accurate stage of the disease and decide future therapy. Although Wilms tumors can often grow to very large sizes at time of detection, most are resectable and radical nephrectomy should almost be the initial therapeutic option unless there are indications of delayed resection.We present a giant right sided Wilms tumor that developed in a 16 months old female, where surgical excision was attempted as the initial therapeutic option and discuss the preoperative evaluation, intraoperative details and immediate postoperative outcome.